EFEKTIVITAS PROGRAM PELATIHAN PARENTING SKILL TERHADAP PENINGKATAN PEMAHAMAN ORANG TUA TENTANG POLA ASUH (Jurnal Bimbingan dan Konseling Islam, 2015)
The aim of this study was to examine the effectiveness of Parenting Skill Training Program to increase understanding of parents about parenting style. Research method used was pre-experiment with pre test – post test design.  Sample of Research was parents of the third class students of MI Husainiyah Pamoyanan, Cicalengka. Chi-Square was used in data analysing to determine the significance of increase understanding of parents about parenting style. The result shows that Parenting Skill Training Programs effectively increased understanding of parents about parenting style. The study offers recommendations for the following parties: First, Madrasah Ibtidaiyah (Islamic Elementary) to be able to implement the program as a serviceguidance for parents. Second, the Guidance and Counseling  Departement and Elementary School Teachers Training Departement of Indonesia university of education need to consider parenting skill studies in relevant subjects. Third, other researchers recommended to extend research variabels and to use varied research methods and design.